Evidence from a Longitudinal Photovoice and Interview Assessment with Congolese Refugee Women in the Midwestern United States (Mary Ann Liebert, 2021)
Purpose: Refugees from the Democratic Republic of Congo have rapidly increased since 2016 and are growing to represent one of the top refugee groups in the United States. They are at high risk for health inequities, yet, there is limited qualitative research exploring the health needs, assets, and experiences of this group and even less longitudinal research. In addition, women refugees are understudied across all global contexts. Therefore, the purpose of this study was to conduct longitudinal qualitative research to provide rich contextual data on health and integration experiences of Congolese refugee women when they were newly resettled in 2016 and 3 years later in 2019. Methods: We conducted photovoice and interviews with 16 women in March through May of 2016 and 10 of the same women in March and April of 2019. Results: Women chose and discussed photos revealing a multitude of assets and needs spanning 2016 and 2019. Experiences with nutrition and food security were illuminated and are the focus of this article. Two major themes were access to food in contrast with availability of abundance of food in the United States and concern about what constitutes healthy food in the United States contrasted with accessing healthy and culturally appropriate food in the United States. Findings highlight strength bases of nutritional knowledge, attitudes, and skills as well as a strong social network aiding food security demonstrated by the Congolese refugee women in the study, offering an opportunity to shift to an assets and strength-based approach. Findings also note risk of food insecurity linked to barriers to employment and sociohistorical reflection on living with food shortages before migration to the United States that should be considered as providers strive to provide culturally relevant care. Conclusion: Findings offer contextual data for health care providers and public health professionals to improve nutritional health promotion and food security support for this population. Overlooking nuanced structural barriers may lead to providers perpetuating health inequities for this population.